Pengaruh Model Pembelajaran Snowball Throwing Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Sitiotio Kabupaten Samosir Tahun Pembelajaran 2023/2024. - Westy Warlianty Siburian; Simion D Harianja; Robert K A Simangunsong; Taripar Aripin Samosir; Damayanti Nababan (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
So that the learning process takes place actively, teachers should use learning models in delivering material according to students' needs. The snowball throwing learning model is a conceptual framework that describes systematic procedures for organizing learning experiences to achieve certain learning goals, and functions as a guide for learning designers and teachers in planning teaching and learning activities.